A conversation with noreen giffney. Issue 1 (2nd January 2023) - Choder-Goldman, Jill
Abstract : In Global Perspectives, we bring you interviews with psychoanalysts from around the world in an effort to explore the influence of culture, politics and socio-economic aspects of the country, and their effect on training, theory development, clinical technique and psychoanalytic practice in general.